A Decade of Olive Oil Tourism: A Bibliometric Survey - Pato, Maria Lúcia (2024)
Olive oil tourism is a recent type of rural tourism; hence, it remains a field of research that is still overlooked. Therefore, it would seem fitting to provide a quantitative overview of the litera‐ ture regarding this promising area. Drawing on an analysis of 42 articles on olive oil tourism in‐ dexed in Web of Science, it becomes clear that olive oil tourism is predominantly a Spanish phe‐ nomenon, as the large majority of authors are affiliated with academic entities located in Spain. The outlets with the highest number of papers published on olive tourism include Sustainability, Tour‐ ism and Hospitality Management and the International Journal of Gastronomy and Food Science,which confirms the multidisciplinarity of said phenomenon. The demand approach and particularly 19 the focus placed on tourists’ psychological traits have garnered considerable attention. In contract, 20 the offer approach is still quite incipient, which hinders the understanding of the strategies used by 21 the stakeholders in the field. Considering the potential that olive oil tourism represents for the sus‐ 22 tainability of rural areas, there is a need for further research in the field, particularly focusing on the 23 product itself and on institutional frameworks and governance.